Effect of Chondroitin Sulfate on Blood Serum Cytokine Profile during Carrageenan-induced Edema and Monoiodoacetate-induced Osteoarthritis in Rats - Korotkyi, Oleksandr; Vovk, Andrii; Blokhina, Oksana; Dvorshchenko, Kateryna; Falalyeyeva, Tetyana; Abenavoli, Ludovico; Ostapchenko, Liudmyla (Reviews on Recent Clinical Trials, 2019)
Background: Blood cytokines affect the development of inflammatory processes in both normal and pathological states. We have studied changes in the concentration of interleukins (ILs) - 1β, IL-4, IL-10, IL-12B p40, transforming growth factor β (TGF β), tumor necrosis factor (TNF-α) in acute carrageenan-induced inflammation and degenerative-dystrophic changes of knee joint caused by monoiodoacetate-induced Osteoarthritis (OA) in experimental models on rats. We also investigated the change in the cytokine profile during prophylactic and therapeutic administration of chondroitin sulfate to animals under experimental conditions. Methods: The concentration of the cytokines was measured in blood serum by enzyme-linked immunosorbent assay. Results: The manifestation of articular lesions was characterized by a disturbance in the balance between proinflammatory (IL-1β, IL-12B p40, TNF-α) and anti-inflammatory (IL-4, IL-10, TGF -β) cytokines. Conclusion: A reduction in the concentration of proinflammatory cytokines in blood serum after prophylactic and therapeutic administration of chondroitin sulfate to the rat with experimental models of acute inflammation of the hind limb and degenerative-dystrophic changes in the knee joint with OA is associated with anti-inflammatory and regenerative properties of the drug.
Keywords: transforming growth factor